Pertimbangan Hakim Atas Penghadiran Bukti Digital Forensik dalam Perkara Kejahatan Fraud - Wahdah Prasetya; Puti Priyana (Wajah Hukum, 2021)
The problems in this research are regulate digital forensic law in proving crime in Indonesia, judges consider the presence of digital forensic evidence in fraud crime. This research uses normative juridical approach, by examining and interpreting matters relating theoretical principles, conceptions, doctrines and legal norms relating to the presence of forensic digital evidence. The result showed that digital Forensic Arrangements in analyzing digital evidence in terms of proving criminal acts are not specifically regulated in the Criminal Procedure Code (KUHAP) because exceptions to electronic / digital evidence are regulated in the Information and Electronic Transaction (ITE) Act so that can be a legal basis for digital forensics. Law No. 11 of 2008 on Information and Electronic Transactions on Article 5 has been clearly stated that electronic information is a valid legal evidence in the form of electronic information and / or electronic documents and / or printout. The rise of data fraud requires a legal arrangement that is expected to be able to prevent and reduce these crimes. For this reason, it is important to elaborate legal arrangements for both implementation and criminal sanctions related to data fraud in Indonesia.